Dosing dilemmas in obese children. Issue 4 (28th June 2010) - Mulla, H; Johnson, T N
Abstract : With the epidemic of childhood obesity, it is not uncommon for prescribers to puzzle over an appropriate drug dose for an obese child. Defining the optimum therapeutic dose of a drug relies on an understanding of pharmacokinetics and pharmacodynamics. Both these processes can be affected by body composition and the physiological changes that occur in obese children. As a rule of thumb, 75% of excess weight in obese subjects is fat mass, and the remainder lean mass. Although it is reasonable to assume that increases in fat mass alter the distribution of lipophilic drugs and increases in lean mass alter drug clearance, good quality and consistent clinical data supporting these assumptions are lacking for the majority of drugs. The relatively few clinical studies that have evaluated the impact of obesity have often been limited by poor design and insufficient sample size. Moreover, clinical studies conducted during drug development rarely include (or are required to include) obese subjects. Guidance on dosing obese children ought to be provided by drug manufacturers. This could be achieved by including obese patients in studies where possible, enabling the effect of body size on pharmacotherapy to be evaluated. This approach could be further augmented by the use of physiologically based-pharmacokinetic models during early (preclinical) development to predict the impact of obesity on drug disposition, and subsequent clinical studies later in development to provide confirmatory proof. In the meantime, for the majority of drugs already prescribed in children, particularly those where the therapeutic range is narrow or there is significant toxicity, the lack of a validated body size descriptor to use at the bedside means the choice of dose will rely on empirical experience and application of the precautionary principle.